2013
DOI: 10.7150/ijms.5385
|View full text |Cite
|
Sign up to set email alerts
|

The Therapeutic Effect of Human Adult Stem Cells Derived from Adipose Tissue in Endotoxemic Rat Model

Abstract: Excessive systemic inflammation following sepsis, trauma or burn could lead to multi-organ damage and death. Bone marrow stromal cells (BMSCs), commonly referred to as mesenchymal stem cells (MSCs), has been studied in several immune-associated diseases in human and animal by modulating the inflammatory response. Adipose tissue derived mesenchymal stem cells (ATSCs), which can be obtained more easily, compared with BMSCs, has emerged as an attractive alternative MSCs source for cell therapy. We investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 42 publications
0
61
1
1
Order By: Relevance
“…with the findings of previous studies (33,34). Differences in results among studies may be associated with the different experimental conditions used.…”
Section: Discussioncontrasting
confidence: 31%
“…with the findings of previous studies (33,34). Differences in results among studies may be associated with the different experimental conditions used.…”
Section: Discussioncontrasting
confidence: 31%
“…The reduction on the levels of anti-inflammatory cytokines was accompanied by the increase on the levels of the anti-inflammatory cytokine IL10 [52,61,[66][67][68][70][71][72]74,76] , although other authors have reported either no effect on IL10 levels or even a reduction [62,63,67,75] . These differences might be related to differences in the experimental settings, such as the use of different animal models, MSCs, dosing and time of sample collection.…”
Section: Effects Of Mscs On Inflammation Induced By Sepsismentioning
confidence: 77%
“…The effects of MSC treatment on survival are a consequence of the reduction of inflammation-associated organ injury and the improvement in organ function. MSC treatment has been reported to reduce damage in kidney (i.e., reduced levels of apoptotic cells, serum creatinine and tubular injury score), liver (i.e., reduced levels of apoptotic cells, serum liver enzymes and blood urea nitrogen), pancreatic (i.e., reduced levels of serum amylase), spleen (i.e., reduced levels of apoptotic cells), lung (i.e., reduced levels of apoptotic cells and vascular leakage) and heart function (i.e., improved cardiac depression) in a variety of sepsis models and experimental settings [61,62,[64][65][66][68][69][70][71][72][73][74][75] . Improvement in organ damage correlates with reduction on neutrophil infiltration and myeloperoxidase (MPO) activity in target organs [52,61] .…”
Section: Mscsmentioning
confidence: 99%
“…Martin et al reported that levels of TNF-α, IL-6 and IL-8 in the serum were higher in newborns who were septic as opposed to newborns who were not (28). Shin et al (29) consistently observed systemic infl ammatory responses such as higher concentrations of proinfl ammatory cytokines TNF-α and IL-6 with LPS, in comparison to control rats. Yanay et al found signifi cantly higher levels of TNF-α, IL-6 and IL-1β in the LPS group than the sham group (30).…”
Section: Discussionmentioning
confidence: 99%